Factors affecting the spatial pattern of bedrock groundwater recharge at the hillslope scale. Issue 21 (27th April 2015) - Appels, Willemijn M.; Graham, Chris B.; Freer, Jim E.; McDonnell, Jeffrey J.; Lin, Henry; McDonnell, Jeffrey; Nimmo, John; Pachepsky, Yakov
Abstract The spatial patterns of groundwater recharge on hillslopes with a thin soil mantle overlying bedrock are poorly known. Complex interactions between vertical percolation of water through the soil, permeability contrasts between soil and bedrock and lateral redistribution of water result in large spatial variability of water moving into the bedrock. Here, we combine new measurements of saturated hydraulic conductivity of soil mantle and bedrock of the well‐studied Panola Mountain experimental hillslope with previously collected (sub)surface topography and soil depth data to quantify the factors affecting the spatial pattern of bedrock groundwater recharge. We use geostatistical characteristics of the measured permeability to generate spatial fields of saturated hydraulic conductivity for the entire hillslope. We perform simulations with a new conceptual model with these random fields and evaluate the resulting spatial distribution of groundwater recharge during individual rainstorms and series of rainfall events. Our simulations show that unsaturated drainage from soil into bedrock is the prevailing recharge mechanism and accounts for 60% of annual groundwater recharge. Therefore, soil depth is a major control on the groundwater recharge pattern through available storage capacity and controlling the size of vertical flux. The other 40% of recharge occurs during storms that feature transient saturation at the soil‐bedrock interface. Under these conditions, locations that can sustain increased subsurface saturation because of their topographical characteristics or those with high bedrock permeability will act as hotspots of groundwater recharge when they receive lateral flow. Copyright © 2015 John Wiley & Sons, Ltd.